Three-dimensional analysis of the takeoff motion in the long jump - Shimizu, Y.; Ae, M. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
The purposes of this study were to investigate why long jumpers laterally leaned at the touchdown of the takeoff using the three-dimensional kinetics analysis and to obtain suggestions for long jumpers` training. The subjects were twelve male university long jumpers. Three-dimentional coordinates and ground reaction forces (GRF) were collected by Vicon cameras and a force platform. The results in this study were revealed that the hip joint of the takeoff leg exerted the large abduction torque during the takeoff as well as hip extension torque (peak hip abduction torque, 4.24±3.28 Nm/kg). The hip abductors seemed to help to bear the body against the GRF and to contribute to obtain the vertical CG velocity. These imply why the long jumpers laterally leaned the body at the touchdown of the takeoff.